When trust breaks: Academic misconduct, innovation networks, and capital discrimination - Hou, Jianxiang; Wang, Kebin; Wu, Tian (Journal of Corporate Finance, 2026)
We investigate how trust shocks affect innovation networks through an incomplete contracting framework. Using academic misconduct cases in China (2015–2021) as an identification strategy, we construct a comprehensive dataset combining patent activities and venture capital investments. We document three key findings. First, academic misconduct triggers persistent declines in university–industry collaboration, reducing both joint patents and citations to university research. Second, affected firms strategically shift toward inter-firm R&D alliances. Third, trust shocks propagate to capital markets, with venture capitalists reducing investments in firms previously linked to universities involved in misconduct. Our findings highlight trust as an irreplaceable mechanism in innovation governance and demonstrate how trust breakdowns reconfigure contractual relationships and resource allocation in innovation networks.